A continuum determination of the strong isospin-breaking contribution to the muon anomalous magnetic moment - Maltman, Kim; Pawley, Christopher James; Lewis, Randy (SciPost physics proceedings, 2025)
First-principles lattice determinations of the Standard Model expectation for the leading order hadronic vacuum polarization contribution to the anomalous magnetic moment of the muon have become sufficiently precise that further improvement requires including strong and electromagnetic isospin-breaking effects. We provide a continuum estimate of the strong isospin-breaking contribution, a_μ^{SIB} a μ S I B , using SU(3) S U ( 3 ) chiral perturbation theory. The result is shown to be dominated by resonance-region contributions encoded in a single low-energy constant whose value is known from flavor-breaking hadronic τ τ decay sum rules. Implications of the form of the result for lattice determinations of a_μ^{SIB} a μ S I B are also discussed.